The pretreatment platelet and plasma fibrinogen level correlate with tumor progression and metastasis in patients with pancreatic cancer. (August 2014) - Wang, Haiyan; Gao, Jinbiao; Bai, Ming; Liu, Rui; Li, Hongli; Deng, Ting; Zhou, Likun; Han, Rubing; Ge, Shaohua; Huang, Dingzhi; Ba, Yi
Abstract Cancer patients frequently present with activated coagulation pathways and thrombocytosis, which are potentially associated with tumor progression and prognosis. However, the prognostic value of abnormal plasma fibrinogen and platelet levels for the treatment of pancreatic cancer is unclear. The purpose of our study was to evaluate the prognostic value of plasma fibrinogen and platelet levels in pancreatic cancer, and to devise a prognostic model to identify the patients with greatest risk for a poor overall survival. One hundred and twenty-five patients diagnosed with pancreatic ductal adenocarcinoma in our hospital between May 2000 and June 2005 were included in this study. The plasma fibrinogen and platelet levels were examined before treatment and analyzed along with patient clinicopathological parameters and overall survival. The foundation of prognostic model was based on the risk factors according to the Cox proportional hazard model. The incidence of hyperfibrinogenemia and thrombocytosis was 24.8% (31/125) and 15.2% (19/125), respectively. The mean fibrinogen concentration differed significantly between the early (I/II) and late (III/IV) stage patients (3.19 ± 0.70 vs. 3.65 ± 0.90 g/l, p = 0.008). Patients with a higher concentration of plasma fibrinogen and platelets had a worse prognosis (p < 0.05). There also existed a significant correlation between higher fibrinogen/platelet levels and distant organ metastasis (p < 0.05, respectively). Bivariate correlation analysis showed that plasma fibrinogen levels correlated significantly with platelet levels (p = 0.000). Multivariate analysis revealed that pretreatment plasma fibrinogen levels (p = 0.027), tumor stage (p = 0.026) and distant metastasis (p = 0.027) were independent prognostic factors. The median survival time for the low-, intermediate-, and high-risk groups was 9.6 months (95% CI 6.2–13.0), 3.8 months (95% CI 2.3–5.3), and 2.3 months (95% CI 0.9–3.7), respectively (p = 0.000). Pretreatment plasma fibrinogen and platelet levels closely correlated with tumor progression, metastasis and overall survival in pancreatic cancer. The foundation of prognostic model may help us identify the greatest risk populations with pancreatic cancer.